134 Do Virtual Conferences Provide Similar Educational Benefit to In-Person Conferences?. (28th February 2022) - McVeigh, J.; Williams, M.
Abstract: Aim: The "Future of Surgery Report" by RCS England concluded that exposure to technological developments and surgical innovation should take place early in medical education to ensure that future surgeons have the broadest skillset possible. In line with these recommendations, in 2019, we developed a platform for the dissemination of knowledge surrounding surgical innovation: the annual Oxford Surgical Innovation (OxSI) Conference. The 2021 OxSI Conference was hosted virtually due to the impact of the COVID-19 pandemic. Method: We sought to compare this event with the previous year to identify if there was any difference in the educational benefit between a virtual conference and an in-person conference. Feedback from delegates was collected using a four-point Likert scale. Results: In 2021, the average scores for the plenary sessions and the workshops were unchanged compared to 2020 (3.6 and 3.5, respectively, p = 0.999). We saw significant differences in our two-outcome metrics, with statistically significant improvement in understanding the practicalities of engaging in safe surgical innovation (Pre 2.70, Post 3.43, +0.73 (P<0.001)) and in awareness of current innovations in surgical practice (Pre 2.77, Post 3.42, +0.65 (P<0.001)). Conclusions: Our data suggest that the virtual format of the conference provided the same educational benefit as the previous in-person iterations of OxSI whilst reaching delegates all over the world. We plan to conduct future OxSI events using a hybrid model and would recommend other conferences consider the same to allow for continued international attendance in conjunction with the benefits of in-person networking and interaction.